Water and Sanitation Services at the Local Government Level in Bangladesh: An Analysis of SDG 6 Implementation Status and Way Forward - Imran Hossain; S. M. Akram Ullah; A. K. M. Mahmudul Haque (Asia Social Issues, 2023)
This study looks into the state of SDG 6 implementation at the local government level in Rajshahi City Corporation (RCC) with a focus on water and sanitation services. The research adopts a mixed-method approach and in-depth interviews to collect primary data. The study analyses the collected data using both quantitative and qualitative techniques. It has been found that large numbers of people do not always have access to enough water, demonstrating the problem of water scarcity in the region. According to the study, only a small percentage of participants tested their drinking water, which suggests that participants were not aware of the importance of water quality. Additionally, the lack of personal water purification and reuse systems is revealed by the research, indicating a gap in sustainable water management practices. Most of the city dwellers expressed dissatisfaction with the authority’s management of the water supply, indicating insufficient oversight and governance. The findings highlight the need for improved infrastructures, water treatment techniques, education campaigns, and governance mechanisms to effectively meet SDG 6 targets and guarantee residents of RCC access to clean water and sanitary facilities.